Salinomycin Induces Autophagy in Colon and Breast Cancer Cells with Concomitant Generation of Reactive Oxygen Species - Verdoodt, Berlinda; Vogt, Markus; Schmitz, Inge; Liffers, Sven-Thorsten; Tannapfel, Andrea; Mirmohammadsadegh, Alireza (PLOS ONE, 2012)
Background Salinomycin is a polyether ionophore antibiotic that has recently been shown to induce cell death in human cancer cells displaying multiple mechanisms of drug resistance. The underlying mechanisms leading to cell death after salinomycin treatment have not been well characterized. We therefore investigated the role of salinomycin in caspase dependent and independent cell death in colon cancer (SW480, SW620, RKO) and breast cancer cell lines (MCF-7, T47D, MDA-MB-453). Methodology/Principal Findings We detected features of apoptosis in all cell lines tested, but the executor caspases 3 and 7 were only strongly activated in RKO and MDA-MB-453 cells. MCF-7 and SW620 cells instead presented features of autophagy such as cytoplasmic vacuolization and LC3 processing. Caspase proficient cell lines activated autophagy at lower salinomycin concentrations and before the onset of caspase activation. Salinomycin also led to the formation of reactive oxygen species (ROS) eliciting JNK activation and induction of the transcription factor JUN. Salinomycin mediated cell death could be partially inhibited by the free radical scavenger N-acetyl-cysteine, implicating ROS formation in the mechanism of salinomycin toxicity. Conclusions Our data indicate that, in addition to its previously reported induction of caspase dependent apoptosis, the initiation of autophagy is an important and early effect of salinomycin in tumor cells.